LONG-TERM RISK OF CHRONIC AND END-STAGE KIDNEY DISEASE AFTER PREECLAMPSIA: SYSTEMATIC REVIEW - Azwar Aziz, Mohamad; Intan Kania, Yulia; Aziz, Ilham; Sibli (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Introduction: Preeclampsia (PE) is a pregnancy-related syndrome, and its diagnosis has evolved to consider factors like hypertension and kidney involvement, with serum creatinine gaining importance. Despite the traditional view of PE as transient and reversible kidney disease, recent studies link it to long-term risks, including cardiovascular and renal diseases. The systematic review, "Long-Term Risk of Chronic and End-Stage Kidney Disease After Preeclampsia," aims to gather updated information from recent studies, focusing on ESRD, CKD, and kidney-related morbidity after PE. The goal is to inform the formulation of effective long-term control and prevention strategies for CKD associated with a history of preeclampsia. Method: The researchers in this study followed the 2020 Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines to ensure that their work met the required standards. This was done to ensure the precision and reliability of the conclusions derived from the research. Result: This systematic review investigated final 16 articles. After looking at the titles and summaries, we found 8 papers that fit our criteria. At first, we excluded several articles because they were written in review style and case reports. But after reading the full papers carefully, we included five papers in our final analysis. These papers included a nation-wide cohort, nationwide register based cohort study, observational cohort study, population-based nested case-control study, and longitudinal cohort study. Conclusion: Our study reveals a significant long-term impact of preeclampsia on kidney health, with a 5-fold higher risk of end-stage kidney disease (ESKD) for affected women. Ongoing clinical monitoring and further research are crucial to identify high-risk individuals, understand underlying mechanisms, and establish optimal follow-up and intervention strategies.